2006
DOI: 10.1007/s00228-005-0089-4
|View full text |Cite
|
Sign up to set email alerts
|

Changing antibiotics prescribing practices in health centers of Khartoum State, Sudan

Abstract: Inappropriate prescribing patterns of antibiotics in health centers of Khartoum State, Sudan, are alarmingly high. Multifaceted interventions involving audit and feedback combined with either academic detailing or seminars appear more effective in changing prescribing practices of antibiotics than audit and feedback alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 20 publications
1
60
0
5
Order By: Relevance
“…Sudan 344 Twenty health centers in Khartoum Dtate were randomly assigned to receive either (a) no intervention; (b) audit and feedback; (c) audit and feedback þ seminar; or (d) audit and feedback þ academic detailing The targeted interventions involving audit and feedback combined with academic detailing reduced the mean number of physician encounters with an antibiotic prescribed by 6.3 and 7.7 (p < .001) at 1 and 3 months post-intervention, respectively. The mean number of encounters where antibiotics were inappropriatetly prescribed were also significantly reduced post intervention (p < .001) Reducing the number of activities reduced the overall impact 298 .…”
Section: Nepalmentioning
confidence: 99%
“…Sudan 344 Twenty health centers in Khartoum Dtate were randomly assigned to receive either (a) no intervention; (b) audit and feedback; (c) audit and feedback þ seminar; or (d) audit and feedback þ academic detailing The targeted interventions involving audit and feedback combined with academic detailing reduced the mean number of physician encounters with an antibiotic prescribed by 6.3 and 7.7 (p < .001) at 1 and 3 months post-intervention, respectively. The mean number of encounters where antibiotics were inappropriatetly prescribed were also significantly reduced post intervention (p < .001) Reducing the number of activities reduced the overall impact 298 .…”
Section: Nepalmentioning
confidence: 99%
“…However, there is lack of information regarding the implementation of pharmaceutical care services in developing countries and its value. Studies carried out in several developing countries including Sudan have shown that prescribing and dispensing practices were frequently irrational and illogical with many inappropriate prescribing practices 16,17,18,19,20,21…”
Section: Introductionmentioning
confidence: 99%
“…2 Several studies from developing countries have described drug use problems that have included polypharmacy, use of drugs that were not related to the diagnosis, patient nonadherence, overuse or misuse of antibiotics, overuse of injections and of relatively safe drugs, and the use of unnecessary expensive drugs. [3][4][5][6][7][8][9][10][11][12][13] Such practices result in a waste of resources, inappropriate patient demand, antimicrobial resistance, and increased drug-related morbidity and mortality. 14 Drug use studies are important tools to assess whether medications are rationally used, with considerations of their efficacy, safety, convenience, and cost.…”
mentioning
confidence: 99%